REINVENTING public administration (1996)
"If there is a constant in American public administration, it is the search for change. Every President in this century has sought in some way to reorganize or reform federal administration or the civil service. Several points are clear. The reinvention has served as a vehicle for synthesizing and expressing ideas and recommendations from different schools of thought and sources about how public administration should be changed: public choice, principal agent theory, total quality management, privatization, marketization, and others. In this forum, eight authors examine aspects of federal reinvention. John M. Kamensky, explains the review's origins, objectives, progress, and current status. He emphasizes that the National Performance Review is an evolving process. Charles Fox interprets reinvention and the National Performance Review as forms of postmodern symbolic politics. He suggests an answer to the question of why reinvention has achieved some popularity, despite its inconsistencies and other shortcomings. If Fox is right, a good part of the National Performance Review is an attempt to manage perceptions. H. George Frederickson puts the National Performance Review in the context of the history of public administration thought in recent decades, comparing reinvention with the New Public Administration. David B. Walker analyzes the movement toward New Federalism III. B. Guy Peters and Donald J. Savoie analyze problems of achieving coherence in policies and programs that cut across departmental lines under radical decentralization and empowerment. James R. Thompson and Patricia W. Ingraham examine the congruence between political models and activities of reinvention labs. Finally, James D. Carroll and Dahlia Bradshaw Lynn assess the future of federal reinvention from congressional perspectives. One point comes through. While federal reinvention has shortcomings and may prove to be a fad or a misdirected effort, the questions it raises are important and warrant continuing thought and work by the public administration community"
Keywords: Public administration - United States; Public administration